Aprehender el desarrollo de las organizaciones en la encrucijada entre el curso de acción y el enfoque instrumental: la perspectiva transicional - Anne Bationo-Tillon; Céline Poret; Viviane Folcher (Universidade do Porto, 2020)
In this paper, we address the question of possible conceptual ways of thinking about organizations in the making. We begin by introducing the concept of border, which seems heuristic to us, to define organizational development as crossing borders. We then propose to consider the border crossing from an intrinsic point of view by adopting a transitional perspective. To address these transitional phenomena, we articulate two conceptual ergonomics frameworks: the course of action and the instrumental approach. Through two contrasting researches from the point of view of the fields of activity (travel narratives and a process of treating a customer demand in the energy field), we confront the ways to hybridize these two theoretical frameworks conceptually, methodologically and empirically. We highlight what results from this hybridization: the so-called transitional instruments that confer continuity to different scales. Finally, we discuss the perspectives opened by a transitional approach to think about organizational genesis.